THE REASON OF APPLYING PREWRITING PHASES OF ARGUMENTATIVE WRITING - Dian . Novita; Berlin . Sibarani; Amrin . Saragih (Universitas Negeri Medan, 2022)
The objectives of this study were to describe the cognitive process occurs during the prewriting phases of argumentative writing among the undergraduate students and to explain why such cognitive process are realized in undergraduate students of prewriting phases in argumentative writing. This study is limited to the study of the cognitive process in prewriting phases for undergraduate students. This study is followed the theory of Kellog (1990:327) about the the activities in prewriting phases consist of (1) Collecting Information, and (2) Planning text. In accordance to the theory and research purposes, descriptive qualitative research design was appropriately implemented in the study. The data of this research were the students’ students utterances, which were collected through semi-structured interviews and interpreted through the Kellog’s Theory. The reason why the students should apply the prewriting phases were: (1) there was misconception of argumentative writing, (2) there was no knowledge about the generic structure of argumentative, (3) there is no awareness that in argumentative writing, the students should talk the controversial part of the topic, and (4) the students do not know that they have to state explicitly their standing point towards an issue and provided the reasons, facts, and empirical evidences. This leads to conclusion that cognitive process in prewriting is important to be applied in students writing process.